Change in immune biomarkers of laboratory mice responding to experimental inoculation of different drinking water quality from selected dairy farms - Faez Firdaus Abdullah Jesse,; Nagachandra Rao Gopi Naidu,; Paul, Bura Thlama; Lim, Eric Teik Chung; Wan Lutfi Wan Johari,; Abba, Yusuf; Mohd Azmi Mohd Lila,; Mohd Jefri Norsidin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Current knowledge of abnormal physiological responses in livestock due to consumption of substandard water is limited. This study was designed to explore the host cell responses in mice orally inoculated with different drinking water qualities from selected dairy cattle farms. A total of 28 female mice used in this study were divided into Group 1- negative control (treated with sterile deionized distilled water), Group 2 - treated with good quality water sample, Group 3 - treated with moderate quality water sample, and Group 4 - treated with unsatisfactory quality water sample. All the mice were given 0.25 mL of water samples three times daily for 30 days. Blood samples were collected from all mice before euthanasia at 30 days post-inoculation for reproductive hormones and biomarkers analyses. All treatment groups showed significant (p<0.05) weight loss compared to the control group. There was a significant difference in the serum immunoglobulin-G (IgG), , immunoglobulin-M (IgM), interleukin-12 (IL-12), haptoglobin (Hp), and serum amyloid A (SAA) profiles of mice among the different water quality treatments as compared to the control group (p<0.05). In conclusion, the host cell responses exhibited by the mice in the treatment groups indicates a high risk of potential negative effect on the production and health of the livestock due to long-term consumption of drinking water with subpar quality.